Coiler mechanism for synthetic fibers (1946)
General view of a coiler mechanism used at DuPont during the early stages of synthetic fiber production and research. Typically, this type of apparatus was used to coil tow, an untwisted bundle of continuous filaments, for storage.
Keywords: Nylon; E.I. du Pont de Nemours & Company; Machinery